Correlation between cytochrome P450 2C19 genetic polymorphism and treatment response to escitalopram in panic disorder. Issue 8 (August 2017) - He, Qianqian; Yuan, Zhuo; Liu, Yuanyuan; Zhang, Jian; Yan, Hong; Shen, Li; Luo, Xingguang; Zhang, Yong
Abstract : Objectives: Escitalopram (S-CT) is used widely to treat patients with panic disorder (PD) and the CYP2C19 enzyme is responsible for S-CT metabolism. We hypothesized that CYP2C19 polymorphisms were associated with S-CT treatment response in Chinese patients with PD. Patients and methods: Seventy-eight patients with PD completed the assessment by the Panic Disorder Severity Scale – Chinese Version (PDSS-CV) and the Hamilton Anxiety Scale (HAMA-14) during an 8-week period. All patients were administered a fixed dose of 10 mg/day S-CT. Three CYP2C19 metabolizer phenotypes were analyzed by PCR-genotyping microarray, including extensive metabolizer (EM), intermediate metabolizer, and poor metabolizer (PM). Results: This prospective, open-label and observational study showed that the proportion of EM (43.6%) was higher than that of PM (10.2%). There were higher response ratios of PDSS-CV in PM (the second to fourth week: 62.5–100%) than in EM (the second to fourth week: 23.5–55.9%) ( P s<0.05); also, there were higher response ratios of HAMA-14 in PM (the second to fourth week: 75.0–100%) than in EM (the second to fourth week: 17.7–52.9%) ( P s<0.05). Treatment response was based on the reduction of PDSS-CV and HAMA compared with the baseline. There was higher reduction of PDSS-CV in the patients with PM (68.78±9.04 for the fourth week and 84.30±9.81 for the eighth week) than EM (49.66±20.77 for the fourth week and 63.12±22.60 for the eighth week) ( P s<0.05); also, there was higher reduction of HAMA-14 in the patients with PM (70.11±8.98 for the fourth week and 81.32±8.25 for the eighth week) than EM (51.51±18.53 for the fourth week and 62.79±18.28 for the eighth week) ( P s<0.05). Conclusion: The CYP2C19 genetic polymorphism is associated with S-CT treatment response in Chinese patients with PD. CYP2C19 PM could play a key role in early treatment response of S-CT.